(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
In this work, the hydrokinetic energy potential of a new part of the Argentinian coastline is assessed. This site is on the surrounding coast of Isla de los Estados, off the eastern tip of the main island of Tierra del Fuego Province. Located at the southernmost part of Argentina, this site is composed of multiple high energetic locations, subdivided into: Le Maire Strait, exposed coastline East of the Isla de los Estados, and fiords inside this island. Here, only Le Maire Strait is analyzed due to its larger size and relevance: it extends for 30 km between the main island of Tierra del Fuego and the west coast of Isla de los Estados with an average depth of 100 m and plays a crucial role for navigation onto the Drake Passage and Antarctica. This first approach replicates former assessments in the region by means of a numerical 2D (depth-averaged) hydrodynamical model made in Delft3D-FLOW. Results were obtained by a nested modelling strategy that accurately propagates astronomical tidal dynamics from open seas onto the shores without disproportionately increasing computational costs. Since the region presents a strong astronomical tidal dominance, even though it might not be the case for this site, no meteorological tide nor waves were included at this stage. Previous works in the region have shown that Patagonian Estuaries have significant tidal energy potential, which, even though is not top rated worldwide, is still of importance and could be harnessed mostly by small to medium devices, and with some areas for larger turbines. On this site, however, mean current velocities higher than 1 m/s are found in large areas (around 30.000 Ha), with over 200 Ha above 1.5 m/s and high-power density (>1.5 kW/m2). Even though no mean current velocities above 2 m/s were found, Le Maire Strait is probably the site with the largest amounts of available power in Argentina for this kind of renewable energy and might be an ideal site once the technology has matured. Finally, a comparison with Alderney Race (France), which is one of the best sites in the world for hydrokinetic energy is made to bring a wider perspective of the hydrokinetic power available on this site.